CFD analysis of the WindEEE dome produced downburst-like winds. Issue 232 (January 2023) - Žužul, J.; Ricci, A.; Burlando, M.; Blocken, B.; Solari, G.
Abstract: Thunderstorm is a severe phenomenon which can produce downburst winds capable for causing significant damage or even the collapse of low-rise structures. Experimental tests and numerical simulations are widely used by the Wind Engineering (WE) community for gaining increased understanding of complex winds like downbursts. In this paper, the accuracy of the Unsteady Reynolds-averaged Navier-Stokes (URANS) and Scale-Adaptive Simulation (SAS) to reproduce a vertical downburst wind - previously tested in the WindEEE Dome wind-simulator facility - was investigated. CFD results were first validated with the experiments and then used to study the dynamics of the phenomenon. The most suitable CFD setting ( i.e. SAS case based on the k-ω SST turbulence model) was able to reproduce the development of the primary vortex ring, shedding of secondary rings induced by Kelvin-Helmholtz (KH) instabilities and the periodic detachments of smaller secondary vortices ahead the primary vortex. The superposition of these three contributions has shown to determine the temporal variation of the characteristic nose-shaped vertical profile which was found in the experiments. The performed simulations were also compared to field measurements from the NIMROD project showing a high level of agreement. Highlights: URANS and SAS simulation can recreate WindEEE Dome produced downburst flow features. The bell-shaped inflow nozzle impacts the development of ring vortices. Secondary vortices (SV) ahead of the primary vortex (PV) are detached by PV rotation. Downburst wind field is determined by PV, trailing ring vortices, and detached SVs. Characteristic nose-shaped velocity profiles are both space and time-dependent.